Disseminated paracoccidioidomycosis under biological therapy - Ibarra-Burgos, Jaime A; Correa-Sierra, Simón; Londoño-Tabares, Sergio A (The Journal of Infection in Developing Countries, 2025)
Introduction: Paracoccidioidomycosis is an endemic mycotic infection caused by Paracoccidioides spp., prevalent in Central and South American countries. Anti-tumor necrosis factor (TNF) alpha agents, commonly used for autoimmune diseases, increase the risk of severe infections. We present a case of anti-TNF alpha-related paracoccidioidomycosis in a 71-year-old male farmer from Colombia. Case presentation: The patient had oral lesions and chronic cough. A biopsy showed granulomatous inflammation with multinucleated giant cells but no microorganisms. Negative microbiological stains and tests for other infections prompted further investigations. A positive serum immunodiffusion test for Paracoccidioides antibodies at a 1:256 titer led to mediastinoscopy and lung biopsy, which revealed budding yeast in a “captain’s wheel” formation. Treatment with liposomal amphotericin B and itraconazole was initiated. Conclusions: This case highlights the risk of opportunistic infections under anti-TNF alpha therapy and raises awareness of paracoccidioidomycosis associations. Early diagnosis and management are essential for better patient outcomes.